Answer:
The value of a = - 1 , And b =
Step-by-step explanation:
Given as :
Function f(x) = ![\frac{(x + a)}{(x + b)}](https://tex.z-dn.net/?f=%5Cfrac%7B%28x%20%2B%20a%29%7D%7B%28x%20%2B%20b%29%7D)
And f(f(1)) = 0 And f(2) = - 3
Now For , x = 2 , y = - 3
I.e f(2) = ![\frac{(2 + a)}{(2 + b)}](https://tex.z-dn.net/?f=%5Cfrac%7B%282%20%2B%20a%29%7D%7B%282%20%2B%20b%29%7D)
or, - 3 =
I.e 2 + a = - 6 - 3b
Or, a + 3b = - 8 ....... 1
Again f(f(1)) = 0
So,
= 0
Or, 1 + a = 0
∴ a = - 1
So , put htis value of a i n eq 1 , we get value of b
So , - 1 + 3b = - 8
Or, 3b = - 7
∴ b =
Hence The value of a = - 1 , And b =
Answer
I think the simplify expression is 2^2 x 7 = 28. Sorry if it is wrong
Answer:
$2916.00
Step-by-step explanation:
Answer:
D. 32 ft^2
Step-by-step explanation:
You find the mean of the two bases 7+9= 16 16/2=8 Then multiply 8 by 4 to get 32 ft ^2